Corrosion of Al-3.5Cu-1.5 Mg–1Si alloy prepared by selective laser melting and heat treatment. (September 2020) - Wang, Pei; Gebert, Annett; Yan, Lei; Li, Haichao; Lao, Changshi; Chen, Zhangwei; Kosiba, Konrad; Kühn, Uta; Scudino, Sergio
Abstract: The corrosion properties of selective laser melted (SLM) and of additionally heat-treated (T6) Al-3.5Cu-1.5 Mg–1Si samples were assessed in 0.001 M and 0.1 M NaCl solutions (pH 7) by means of electrochemical polarization measurements and SEM surface analysis. In both solutions these new alloy types exhibited improved corrosion behavior compared to wrought and heat-treated AA 2024 reference states. This is attributable to more refined microstructural states and to the formation of particular phases. The SLM samples comprise finely dispersed Q-phase particles which act cathodic and thus, trigger adjacent matrix phase dissolution. Additional T6 heat treatment was efficient for attaining the lowest corrosion current density of ~0.04 μA/cm 2 and a widening of the anodic passive range to ~400 mV in 0.1 M NaCl. Only this alloy state shows a repassivation ability upon reverse scanning. T6 treatment yields mainly the Mg2 Si phase acting as local anode and a widely passive Al-based matrix phase. Altogether, SLM processing with final heat treatment of the Al-3.5Cu-1.5 Mg–1Si alloy is suitable for achieving not only superior mechanical performance but also improved corrosion stability. Graphical abstract: Image 1 Highlights: SLM and heat-treated (T6) Al-3.5Cu-1.5 Mg–1Si with refined microstructure, new phases. New SLM alloys with better corrosion behavior than wrought AA2024 in NaCl solutions. SLM samples with dispersed Q phase acting as cathode, triggering matrix dissolution. T6 treated SLM alloy with best corrosion performance and repassivation ability. T6 treated SLM alloy with Mg2 Si phase as local anode, widely passive Al-rich matrix.